The psychologist's companion for undergraduates : a guide to success for college students - Sternberg, Robert J.; Sternberg, Karin, 1976- (Cambridge : Cambridge University Press, 2017)
Tailored specifically for undergraduate students, this Companion offers uniquely comprehensive coverage of the topics necessary for successful communication in psychology, making it a valuable resource for research methods and introductory psychology courses. Readers will learn how to effectively plan and write papers in accordance with the latest style guidelines from the Publication Manual of the American Psychological Association, Sixth Edition; present data in posters and talks; and evaluate their own and others' work. The clear writing style and reader-friendly format, meanwhile, allow students to absorb information easily, even when reading chapters selectively or out of order. The book includes numerous up-to-date examples drawn from career experiences to engage students and help them apply what they've learned to forward their own careers, while questions encourage them to think more deeply about larger issues in the field, preparing them for future research.
Title from publisher's bibliographic system (viewed on 13 Aug 2019).
Keywords: elektronické knihy; electronic books; Report writing -- Handbooks, manuals, etc; Psychology -- Authorship -- Handbooks, manuals, etc